Regulatory effect of rat bone marrow mesenchymal stem cells on Treg/Th17 immune balance in vitro - Wang, Kai (Mol Med Rep, 2020)
Bone marrow mesenchymal stem cells (BM-MSCs) regulate the balance between regulatory T cells (Tregs) and T helper 17 (Th17) cells. However, the role of different factors on BM-MSCs-mediated regulation of the Treg/Th17 balance is unknown. BM-MSCs and CD4(+) T lymphocytes were co-cultured with various treatments. The ratio of Treg/Th17 cells was calculated and the expression of different cytokines was measured. BM-MSCs were found to have a proliferative effect on Th17 cells at a basal concentration and at a 2-fold increase in the number of BM-MSCs. However, when the number of BM-MSCs used was increased 4-fold, they had an inhibitory effect on the Th17 cells. The effect of BM-MSCs on Tregs was inhibited by the addition of tacrolimus but not rapamycin. The effect of BM-MSCs on Th17 cells was inhibited by rapamycin. Additionally, the effect of BM-MSCs on Tregs were inhibited by the addition of a transforming growth factor-β (TGF-β) blocker, whereas these TGF-β-blockers had no effect on Th17 cells. Addition of an interleukin (IL)-2 blocker reduced the proportion of Th17 cells when co-cultured with a high number of MSCs compared with the low concentration group and the proportion of Treg cells was significantly decreased when cells were treated with an IL-2 blocker compared with the control group. Together, these results showed the varying effects of MSCs on the ratio of Treg/Th17, its dependence on the number of MSCs and the effects of cytokines in inducing these changes in the balance.